Smith‐Lemli‐Opitz syndrome — Fetal phenotypes with special reference to the syndrome‐specific internal malformation pattern. Issue 2 (16th December 2019) - Schoner, Katharina; Witsch‐Baumgartner, Martina; Behunova, Jana; Petrovic, Robert; Bald, Rainer; Kircher, Susanne G.; Ramaswamy, Annette; Kluge, Britta; Meyer‐Wittkopf, Matthias; Schmitz, Ralf; Fritz, Barbara; Zschocke, Johannes; et al.
Abstract: Background: Autosomal‐recessive SLOS is caused by mutations in the DHCR7 gene. It is defined as a highly variable complex of microcephaly with intellectual disability, characteristic facies, hypospadias, and polysyndactyly. Syndrome diagnosis is often missed at prenatal ultrasound and fetal autopsy Methods: We performed autopsies and DHCR7 gene analyses in eight fetuses suspected of having SLOS and measured cholesterol values in long‐term formalin‐fixed tissues of an additional museum exhibit Results: Five of the nine fetuses presented classical features of SLOS, including four cases with atrial/atrioventricular septal defects and renal anomalies, and one with additional bilateral renal agenesis and a Dandy‐Walker cyst. These cases allowed for diagnosis at autopsy and subsequent SLOS diagnosis in two siblings. Two fetuses were mildly affected and two fetuses showed additional holoprosencephaly. These four cases and the exhibit had escaped diagnosis at autopsy. The case with bilateral renal agenesis presented a novel combination of a null allele and a putative C‐terminus missense mutation in the DHCR7 gene Conclusions: In view of the discrepancy between the prevalence of SLOS among newborns and the carrier frequency of a heterozygous DHCR7 gene mutation, the syndrome‐specific internal malformation pattern may be helpful not to miss SLOS diagnosis in fetuses at prenatal ultrasound and fetal autopsy